Temporal trends in transcatheter aortic valve implantation, 2008–2014: patient characteristics, procedural issues, and clinical outcome. Issue 2 (26th October 2016) - Landes, Uri; Barsheshet, Alon; Finkelstein, Ariel; Guetta, Victor; Assali, Abid; Halkin, Amir; Vaknin‐Assa, Hanna; Segev, Amit; Bental, Tamir; Ben‐Shoshan, Jeremy; Barbash, Israel M.; Kornowski, Ran
Abstract : Background: About a decade past the first transcatheter aortic valve implantation (TAVI), data are limited regarding temporal trends accompanying its evolution from novel technology to mainstream therapy. We evaluated these trends in a large multicenter TAVI registry. Hypothesis: TAVI is changing and improving with time. Methods: Patients who underwent TAVI between January 2008 and December 2014 at 3 high‐volume Israeli centers were divided into 5 time quintiles according to procedure date. Outcomes were analyzed and reported according to Valve Academic Research Consortium‐2. Results: A total of 1285 patients were studied (43% male; mean age, 83 ± 3 years; mean Society of Thoracic Surgeons [STS] score, 5.5 ± 3.6). Over time, there was a shift toward treating patients at lower STS score, increased use of conscious sedation and transfemoral approach, and decreased use of balloon predilatation. The balloon‐expandable to self‐expandable valve utilization ratio decreased, the valve‐in‐valve experience increased from 4% to 17% of all TAVI volume, and length of hospital stay was halved ( P = 0.006). Kaplan‐Meier survival curves showed gradual decrease in mortality risk ( P = 0.031), but there was no significant 1‐year mortality decrease by multivariable analysis. Each year increment was associated with an adjusted 20%, 15%, and 12% decrease in new pacemaker obligation ( P = 0.004), new pacemaker obligation or left bundle branch block ( P = 0.008), and in‐hospital infections ( P = 0.082), respectively. Conclusions: Temporal trends accompanying TAVI evolution include its utilization in lower‐risk patients, procedural simplification, improved overall survival, decreased pacemaker obligation, and shorter hospital stay.